Survei Minat Siswa Kelas VIII di SMPN 2 Rawamerta dalam Pembelajaran Renang Berdasarkan Jenis Kelamin - Furqan Shosa; Saeful Ma’mun; Ruslan Abdul Gani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine how high the interest of class VIII students in learning swimming at SMPN 2 Rawamerta, Karawang Regency is. This research is a quantitative descriptive. The method used in this study is a survey method, the instrument is a questionnaire, the subjects in this study are class VIII students of SMPN 2 Rawamerta, totaling 84 people. The data analysis technique used quantitative descriptive analysis as outlined in the percentage. The results of this study indicate that the level of knowledge of class VIII students towards swimming learning is in the categories of "very low" 7.14%, "low" 30.95%, "medium" 28.57%, "high" 30.95%, and “very high” 2.38%.